Development of airbag suit system for motorcyclist - Zainal Abidin, Zulkifli; Razali, Fakhruddin (INSI Publications, 2014)
Airbag suit is proven to prevent motorcyclists from having serious injuries especially spine, neck, ribs and collar-bone fractures. A common way to inflate the airbag is by attaching one part that called pin to the valve that controlling the airflow from canister to the airbag. An airbag inside inflated automatically when a pin connecting the jacket to the bike was pulled from its socket forcefully. However, unnecessarily inflation by a simple collision or falling down from the motorcycle waste the canister and replacing it is costly. The simple pull mechanism adds substantial delay to the system response which is undesirable during the impact. Thus, sensors activated valve is proposed to replace the mechanism. The project involved development of a control algorithm for the airbag inflation and performing analysis on the finished prototype. The system takes the inputs from IMUs and GPS for G-force and speed calculation. When a rider’s position changed rapidly relative to the equilibrium position which is initially set during the calibration, the airbag will inflates. The calibration involved a sizable collection of samples, analysis and training to set the threshold in the algorithm which decides the emergency events. The implementation of sensory system reduces the response time which is critical during the impact.